How should we define clinically significant improvement on Patient-Reported Outcomes Measurement Information System (PROMIS) for patients undergoing Knee Meniscal Surgery?. Issue 7 (31st July 2020) - Lu, Yining; Nwachukwu, Benedict; Beletsky, Alexander; Patel, Bhavik; Yanke, Adam; Verma, Nikhil; Cole, Brian; Bush-Joseph, Charles; Bach, Bernard; Forsythe, Kelechi Okoroha Brian
Objectives: The Patient-Reported Outcomes Measurement Information System (PROMIS) attempts to optimize patient reported outcome (PRO) instruments by utilizing item response theory (IRT) and computer adaptive testing (CAT). Relatively little is known about clinically significant outcome (CSO) improvements on the PROMIS Physical Function (PF) CAT. The objective of this study is to define the minimal clinically important difference (MCID), substantial clinical benefit (SCB) and patient-acceptable symptom state (PASS) of the PROMIS PF CAT in arthroscopic meniscal surgery. Methods: The PROMIS PF CAT, Short Form-12 Health Survey (SF-12 physical health [PCS] and mental health [MCS]), Veterans Rand-12 Health Survey (VR-12 physical health [PH] and mental health [MH]), and the Marx Activities Ratings Scale were administered pre- and post- operatively to patients undergoing arthroscopic meniscal surgery. Six months postoperatively, patients graded their knee function based on a domain-specific anchor question. Answers to the anchor questions were dichotomized to indicate achievement of SCB and MCID. A satisfaction anchor question was used to indicate achievement of PASS. Receiver operating characteristic (ROC) analysis determined the relevant psychometric values. Cutoff analysis was performed to find preoperative PRO scores predicting CSO achievement. Results: Sixty patients (N = 27, 45% female) were included, with mean age of 45.0 ± 14.0 years and average follow up of 24.0 + 1.2 weeks. The most common indication for knee arthroscopy was partial meniscectomy (N = 53; 88.3%) followed by meniscal repair (N = 7; 11.7%). MCID on PROMIS PF was calculated to be 2.08 (AUC: 0.75, 95% CI: 0.57 - 0.94). Net score improvement equivalent to achievement of SCB was found to be 7.41 (AUC: 0.77, 95% CI: 0.55 – 0.99). PASS was found to be 45.47 (AUC: 0.89, 95% CI: 0.79-0.99). Preoperative score below 37.6 on the PROMIS PF CAT predicted achievement of MCID (AUC: 0.76, 95% CI: 0.64-0.88), while scores above 41.7 predicted achievement of PASS (AUC: 0.76, 95% CI: 0.63-0.89). Absence of pre-existing arthritis and higher baseline functional status were also found to be statistically significant predictors of achieving CSOs. Conclusion: Our study defined MCID, SCB, and PASS, for the PROMIS PF CAT. We found that a pre-operative score below 37.6 was predictive for achieving a meaningful clinical change with surgery, while a pre-operative score above 41.7 was predictive of achievement of an acceptable post-operative health state. Table 1. Patient Demographic and Perioperative Variables N Percent Total patients 60 Age (Mean±SD) 45.0±14 Male 33 55 Worker's Compensation 10 16.7 Right-sided 28 46.7 Diabetes 5 8.3 Depression 9 15 Hypertension 10 16.7 Alcohol 35 58.3 Smoking Never 53 88.3 Former 5 8.3 Current 2 3.3 Days of Exercise Per Week (Mean±SD) 2.57 2.05 History of Narcotics Use within Three Months of Surgery Date (%) 4 6.7 Tear Location Both 7 11.7 Medial 43 71.7 Lateral 10 16.7 Tear Type Horizontal Cleavage 9 17.6 Oblique 2 3.9 Peripheral 4 7.8 Degenerative 11 21.6 Flap Tear 5 9.8 Radial 5 9.8 Complex 9 17.6 Root Tear 3 5.9 Bucket Handle 3 5.9 Chronicity* Traumatic/Acute 24 40.0 Chronic 36 60.0 Pre-Existing Arthritis^ 36 60.0 Surgery Type Partial Menisectomy 53 88.3 Meniscal Repair 7 11.7 Root Repair 2 3.3 Number of Caritlage/Chondral Defects (Mean±SD) 1.22±1.17 Location of Cartilage Defect MFC 17 28.3 LFC 8 13.3 Trochlea 16 26.7 Patella 18 30.0 MTP 2 3.3 LTP 4 6.7 *Injuries were determined to be acute if they had occurred within three months of the date of surgery. ^Patients were determined to have preexisting arthritis by intraoperative surgeon determination based on the International Cartilage Repairs Society Classification (ICRS), grade II or greater were deemed arthritis. Table 2. Univariate analysis of demographic variables after stratification by achievement of CSOs based on score on the PROMIS PF CAT MCID SCB PASS Not Achieved (28) Achieved (32) P-value Not Achieved (38) Achieved (22) P-value Not Achieved (31) Achieved (29) P-value Age (Mean±SD) 44.59±15.52 45.42±12.78 0.82 45.11±14.85 44.90±12.74 0.96 47.28±14.42 42.63±13.37 0.20 Male, % 16 (57.1) 17 (53.1) 0.96 19 (50.0) 14 (63.6) 0.45 15 (48.4) 18 (62.1) 0.42 Worker's Compensation, % 3 (10.7) 7 (21.9) 0.42 5 (13.2) 5 (22.7) 0.55 8 (25.8) 2 (6.9) 0.11 Brief Resilience Scale Score (Mean±SD) 3.81±0.58 3.93±0.76 0.51 3.82±0.70 3.98±0.65 0.36 3.87 (0.69) 3.89 (0.67) 0.93 Right-sided % 14 (50.0) 15 (46.9) 1 17 (44.7) 12 (54.5) 0.64 15 (48.4) 14 (48.3) 1 Diabetes, % 1 (3.6) 4 (12.5) 0.44 2 (5.3) 3 (13.6) 0.52 3 (9.7) 2 (6.9) 1 Depression, % 5 (17.9) 4 (12.5) 0.83 6 (15.8) 3 (13.6) 1 5 (16.1) 4 (13.8) 1 Dyslipidemia, % 1 (3.6) 1 (3.1) 1 1 (2.6) 1 (4.5) 1 2 (6.5) 0 (0.0) 0.50 Hypertension, % 7 (20.6) 3 (11.5) 0.56 8 (21.1) 2 (9.1) 0.40 5 (16.1) 5 (17.2) 1 Alcohol, % 17 (60.7) 18 (56.2) 0.93 22 (57.9) 13 (59.1) 1 16 (51.6) 19 (65.5) 0.41 Smoking, % 0.38 0.47 0.33 Never 26 (92.9) 27 (84.4) 35 (92.1) 18 (81.8) 29 (93.5) 24 (82.8) Former 2 (7.1) 3 (9.4) 2 (5.3) 3 (13.6) 1 (3.2) 4 (13.8) Current 0 (0.0) 2 (6.2) 1 (2.6) 1 (4.5) 1 (3.2) 1 (3.4) Days of Exercise Per Week (Mean±SD) 2.25±2.10 2.84±2.00 0.27 2.21±2.16 3.18±1.74 0.08 2.29±2.16 2.86±1.92 0.29 Narcotics Use, % 2 (7.1) 2 (6.2) 1 3 (7.9) 1 (4.5) 1 3 (9.7) 1 (3.4) 0.65 Table 3. Multivariate results of contributors of postoperative score and achievement of CSOs in the PRMOS PF CAT after meniscal surgery Significant Contributor Odd Ratio Confidence Interval P-Value Postoperative PROMIS PF CAT Preoperative Marx Activity Ratings Scale 2.07 1.28-3.36 0.005 PASS Preoperative Marx Activity Ratings Scale 1.19 1.04-1.36 0.014 MCID Preoperative PROMIS PF CAT 0.79 0.63-0.99 0.039 Preoperative KOOS QoL Subscore 1.16 1.02-1.31 0.021 Preoperative KOOS Symptoms Subscore 0.90 0.81-0.99 0.029 Preoperative arthritis 0.0003 5.33E-07-0.13 0.009 SCB Preoperative PROMIS PF CAT 0.82 0.69-0.96 0.017 Days of Exercise per Week 1.87 1.14-3.06 0.013 Preoperative arthritis 0.11 0.02-0.69 0.019 Figure 1.